The Road Less Traveled: A Case Report on Intestinal Behçet’s Disease - Madulara, Glaiza; Gonzalez-Andaya, Pilar Agnes (Philippine Journal of Allergy, Asthma and Immunology, 2022)
Behçet’s Disease (BD) is a rare, chronic, systemic vasculitis with diverse manifestations. The patient was a 29-year-old male with a 10-year history of recurrent oral ulcers and gastrointestinal symptoms, managed as different clinical scenarios prior to reaching a final diagnosis of Intestinal BD. Though BD is a diagnosis of exclusion, it should be included in the differential diagnoses of systemic disorders presenting with recurrent oral ulcers.